2018
DOI: 10.1007/s00520-018-4379-7
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care and psychosocial care in metastatic non-small cell lung cancer: factors affecting utilisation of services and impact on patient survival

Abstract: The rate of PC and PSC in our metastatic NSCLC population was high when compared with published data. Despite this, there were gaps in PC and PSC provision in this population, notably with patients not receiving active treatment, and those receiving systemic therapy utilising these services less frequently. PSC and PC contact were not convincingly associated with improved patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
5
13
0
Order By: Relevance
“…The 6-month, 1-year, and 2-year overall survival rates of the 102 patients with metastatic NSCLC were 17.65%, 3.92%, and 0.98%, respectively. The median overall survival of the 102 patients was 3.15 months ( Figure 2), which was consistent with that in previous studies, which reported a median overall survival of 3-5 months (24)(25)(26). These results provide greatly important basic survival data to researchers evaluating new treatment strategies for patients with recurrent stage III/IV NSCLC who show progression on multiple conventional treatments.…”
Section: Overall Survival Analysis Of All Patients With Advanced Stagsupporting
confidence: 89%
“…The 6-month, 1-year, and 2-year overall survival rates of the 102 patients with metastatic NSCLC were 17.65%, 3.92%, and 0.98%, respectively. The median overall survival of the 102 patients was 3.15 months ( Figure 2), which was consistent with that in previous studies, which reported a median overall survival of 3-5 months (24)(25)(26). These results provide greatly important basic survival data to researchers evaluating new treatment strategies for patients with recurrent stage III/IV NSCLC who show progression on multiple conventional treatments.…”
Section: Overall Survival Analysis Of All Patients With Advanced Stagsupporting
confidence: 89%
“…When discussing the implementation of palliative care, the advanced cancer population is often treated as a single entity. [3][4][5][6] However, as treatment for cancer advances and the life expectancy of many patients with advanced cancer increases, the needs of these patients should not be assumed homogenous. Our data clearly demonstrate a unique population of patients with severe disease who died within 6 months of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…healthcare that focuses on optimal management of pain and other symptoms while incorporating psychosocial and spiritual care according to patient/family needs, values, beliefs and cultures.'' 1 This philosophy has been implemented in a variety of ways in oncology practices around the world [2][3][4][5][6][7][8][9][10][11][12][13][14] and has been shown to improve patient outcomes, including decreased symptom severity, improved quality of life, and in some cases, decreased utilization of emergency department (ED) and hospital admissions. [15][16][17] The study by Temel et al (2010) showed improvement in quality of life, and notably increased survival in patients with advanced lung cancer when palliative care was introduced early in the course of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Performance status, serum lactate dehydrogenase, C-reactive protein, presence of liver/adrenal gland metastases, and extrathoracic disease status significantly predicted survival and formed the basis of the score. Early palliative and supportive care rather than palliative radiotherapy may also be appropriate for patients with many adverse prognostic features [16]. Depending on prognosis, the goal of treatment, target volume size, and lung dose, the authors continue to prescribe 10 or 13 fractions of 3 Gy or, together with Carboplatin/Vinorelbine, 15 fractions of 2.8 Gy.…”
Section: Discussionmentioning
confidence: 99%